(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Male infertility accounts for half of the reported infertility cases worldwide. Acupuncture serves as an alternative therapy for treating gynecological disorders and improving sperm quality. Case presentation We present two Indonesian male infertility patients, aged 32 and 29, diagnosed with oligozoospermia and teratozoospermia, respectively. Both patients underwent electroacupuncture (EA) therapy twice a week for 12 sessions and took oral supplements such as coenzyme, L-carnitine, and alpha-lipoic acid once daily for six weeks following the initial EA therapy. Sperm analysis was conducted before and after EA therapy. Conclusion Our findings suggest that EA therapy and oral supplements may complement conventional treatments for male infertility. However, additional studies with larger sample sizes and longer follow-up periods are necessary to confirm the effectiveness of EA therapy in enhancing sperm quality and fertility outcomes in male infertility patients. BJMS, Vol. 25 No. 02 April’26 Page: 659-665